Development potential of pharmaceutical industry in transition countres - Dickov, V.; Igic, S. (Scientific Journal of Medical Science, 2013)
Contemporary medicine is striving to bring man closer to the ideal of eternal life. This ideal is, of course, unattainable within the boundaries of currently existing knowledge, but the breakthroughs in extending life expectancy and enhancements of the quality of life due to medicine and pharmacy are undisputable facts. Just like economic theory recognizes the theory of welfare as a material dimension, it would be necessary to introduce the category of wellbeing, which could illustrate man's need for a long and fulfilled life free from biological limitations. As a logical introduction to considerations on the issue, which addresses the specific features and applications of marketing in pharmaceutical industry, one is faced with a compelling need for a clear identification of reasons that speak affirmatively in favor of the need for deeper and more systematic elaboration of this subject.